An enhanced single phase quasi Z-source switched capacitor seven level inverter with modified SPWM for PV applications - Semko Hosseini; Seyed Hossein Hosseini; Mehran Sabahi; Ebrahim Babaei (Scientific Reports)
Abstract The combination of impedance source networks with switched capacitor multilevel inverters (SC-MLIs) can address the inrush current problem, enhance voltage-gain, and improve immunity which is came from Z-source topology. This paper proposes an improved symmetric single-phase transformerless quasi-Z-Source based on switched capacitor 7-Level inverter (qZ-SC7LI) with a modified modulation technique. The circuit configuration of the qZ-SC7LI is meticulously designed to completely eradicate the issue of leakage current. To address the limited number of shoot-through (ST) states at the zero-voltage level in the proposed topology, a modified modulation technique has been developed. This technique creates ST states at various other voltage levels. Implicitly, this technique reduces the variation of the inverter output voltage (Δv). Furthermore, the qZ-SC7LI can handle reactive power, and continuously derive current from input DC source. Owing to developing stair case output voltage and needing low value for ST duty-ratio (d) the total harmonic distortion (THD) of injected current to the grid is improved and filter size is reduced. The proposed topology is verified by simulation in PSIM software. For experimentally verification of the proposed topology properties, related studies on a 1.2kVA-Lab-scale prototype are carried out.